2D Sandwich-like Sheets of Iron Oxide Grown on Graphene as High Energy Anode Material for Supercapacitors - Qu, Qunting; Yang, Shubin; Feng, Xinliang (Advanced materials (Weinheim), 2011)
2D sandwich‐like sheets of iron oxide grown on graphene as high energy anode material for supercapacitors are prepared from the direct growth of FeOOH nanorods on the surface of graphene and the subsequent electrochemical transformation of FeOOH to Fe3O4. The Fe3O4@RGO nanocomposites exhibit superior capacitance (326 F g−1), high energy density (85 Wh kg−1), large power, and good cycling performance in 1 mol L−1 LiOH solution.